Understanding the nature of sacred space from the African traditional religious perspective : challenges of spatial management - Zenani, Vuyisile John (Department of Religious Studies, 2014)
This study aims to explore the challenges that face land use and land management in the context of the new South Africa. Approached from the African traditional religious angle the study will propose, among others, a new approach to land management and land designation. The study draws insights from literature on religious meaning of land and interviews conducted with two African traditional healers from two different black communities. The study introduces a new concept in land management, the concept of sacred space.